The Effect of Motivational Interviewing-Based Counseling on Women's Sexual Satisfaction and Body Image - Fatemeh Zangeneh; Seyedeh Zahra Masoumi; Arezoo Shayan; Nasrin Matinnia; Hossein Mohagheghi; Younes Mohammadi (Mashhad University of Medical Sciences, 2019)
Abstract It is a widespread recognition that breast cancer adversely affects the lives of many women the world over. Surgeries leading to breast loss (mastectomy) exert a negative impact on body image, sexual drives, and quality of life among women with breast cancer. The present study aimed to examine the effect of motivational interviewing-based counseling on sexual satisfaction and body image of women with mastectomy. This clinical trial was performed on 60 breast cancer patients (two groups of 30) admitted to Imam Khomeini Clinic in Hamedan, Iran. The patient in both groups completed the index of sexual satisfaction (Hudson) and a self-reported questionnaire entitled " Life After Mastectomy". Thereafter, they participated in five training sessions with a motivational interviewing (MI) approach on sexual disorders and body image for the subjects in the intervention group.  In light of the results, a significant difference was found between the intervention group and the control group in terms of the mean sexual satisfaction and body image scores (P<0.001). It is recommended that the MI approach be used to improve sexual satisfaction and body image in patients with mastectomy.